f(x) = ex and g (x) = loge x
Now, fog(x) = f(g(x)) = f(loge x) = elogex= x
⇒ fog(x) = x
gof(x) = g(f(x)) = g(ex) = loge ex = x
Hence, fog(x) = x and gof(x) = x
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation